تضاؤل نسبة الطلاب الذكور في الجامعات الحكومية الماليزية : دراسة تحليلية لعوامله وآثاره وحلوله من المنظور القرآني - Mohammad Fakrulrazi bin Abdullah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The phenomenon of decreasing male students in Malaysian public universities is increasingly on the rise leading to various problems in Malaysian society. The aim of this thesis is to study this phenomenon with a view to investigate the main reason for the decrease in the number of male students in Malaysian public universities. The study also attempts to identify possible solutions to this phenomenon in the light of the Holy Quran. The methodology applied in this study is analytical in nature. This study is composed of three dimensions: (1) explanation of factors that cause this problem by looking at the history of universities along with the history of the development of the education system, (2) analysis of effects towards the family institution and community, (3) the search for solutions to the problem in a light of the Holy Quran and the interpretation from previous and contemporary mufassir. The research concludes that the largest factors contributing to the decreasing number of male students in Malaysian public universities is due to the system of education, that eases the acception of female students the university compared to male students. This study attempts to testify and further demonstrate that the negative impacts of this phenomenon have surpassed its positive impacts. Through the enlightenment from the Holy Quran, there are also preventive measures proposed in the handbook, suggesting that Malaysian society may save itself from further damage by following and acting in manners that have been outlined by The Creator based on what is mentioned in the Holy Quran. In addition to that, it also aims towards explaining the fact that this phenomenon contributes to negative effects towards the family and society leading to the decrease in the feelings of masculinity as defined by Malaysian society. The researcher presents a multitudinous array of paths and intermediaries which in the perspective of the Quran, are capable of addressing of masculinity. With these in mind, it is irrefutable that by seeing the Holy Quran as the main guide in life, and further practicing the guidance emphasized in it, mankind is capable of achieving a profound and gratifying life.